Sustainable enhancement of purple corn traits using Azospirillum brasilense–glomus iranicum var. tenuihypharum inoculants: Evidence from andean agroecosystems – Perú - Rondinel Huanco, Bill (2025)
Purple corn (Zea mays L.), a traditional Andean crop valued for its high anthocyanin content and increasing relevance in the nutraceutical industry. However, its production is challenged by envirmental stress and the overuse of chemical fertilizers in Andean ecosystems. This study evaluated the effects of co-inoculation with Azospirillum brasilense (a plant growth-promoting rhizobacterium, PGPR) and Glomus iranicum var. tenuihypharum (an arbuscular mycorrhizal fungus, AMF) on growth and yield performance in five purple corn genotypes under highland field conditions in Ayacucho,Peru. A randomized complete block design with three replications was implemented across two locations to compare a control (no inoculation) with individual and combined microbial treatments. Results showed that combined inoculation significantly improved vegetive parameters, ear and yield-related traits in both locations, with increases of up to 60.8% in grain yield compared to the control. Statistically significant differences were observed among treatments and genotypes (Tukey, p < 0.05), with the Canaán location showing the highest overall performance between control and combined microbial treatments. These findings support the potential of PGPR-AMF consortia to sustainably enhance purple corn productivity and resilience, offering a viable alternative to reduce chemical inputs in Andean agriculture.